Rural Women in Livestock and Fisheries Production Activities: an Empirical Study on Some Selected Coastal Villages in Bangladesh - Rashid , Md. Mamun-ur; Gao , Qijie (Asian Journal of Agriculture and Rural Development, 2012)
Progressive participation of women in agriculture is evident throughout the Globe. Their participation in fisheries and livestock sector is well recognized but less perceived due to paucity of sufficient data. Considering this fact the present study had been designed to examine women’s participation in fisheries and livestock activities as well as influence of selected socio-economic factors on their participation in some selected coastal villages of Bangladesh. For achieving research objectives a well structured interview schedule was administered on 70 randomly selected rural women during the period of September, 2010. Descriptive statistics exhibit that almost three quarter of the respondents had moderate to high level participation in fisheries and livestock activities. Among the fisheries related activities women had highest participation in feed application (M=1.528) while cleaning cattle shed (M=2.914) and giving feed to poultry birds (M=4.571) occupied the top ranks for cattle and poultry related activities. According to correlation estimates agricultural knowledge and family size had strong positive correlation with women’s participation where as education and family income had negative significant correlation with women’s participation in fisheries and livestock activities. Stepwise multiple regression mirrored that family size, agricultural knowledge and education jointly contribute to 25.6% variance in women’s participation in fisheries and livestock activities.